BACKGROUND OF CONTEMPORARY HINDI DRAMA - Rai, Shashikant (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Both external and internal elements of the object (power) play an important role in shaping the contemporary sentiment. Literature and society complement each other. There has been a huge change in the perspectives of understanding society. For example, keeping the economic system of society at the center, Marxism gave a new perspective of explaining. According to Marx, the economy of society is the base and politics, religion, culture or philosophy are the superstructure. As the base changes, the social structure also changes. Another western scholar 'Ten' talked about understanding literature from a scientific point of view. He believed that caste, environment, and moment, all three play an important role in explaining a creation or an event.